2022
DOI: 10.3390/ijms231911724
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenic Roles of Heparan Sulfate and Its Use as a Biomarker in Mucopolysaccharidoses

Abstract: Heparan sulfate (HS) is an essential glycosaminoglycan (GAG) as a component of proteoglycans, which are present on the cell surface and in the extracellular matrix. HS-containing proteoglycans not only function as structural constituents of the basal lamina but also play versatile roles in various physiological processes, including cell signaling and organ development. Thus, inherited mutations of genes associated with the biosynthesis or degradation of HS can cause various diseases, particularly those involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“… 34 Thus, clearance of HS from the brain at early disease stage might prevent the initiation of this pathogenic cascade. 20 , 31 In fact, the removal of deposited HS by JR-171 suppressed pathological changes in the brain and further prevented the loss of spatial learning ability in the Morris water maze test. Notably, in the 31-week treatment study, neuroinflammation and neurodegeneration were already present at the baseline (11 weeks of age), indicating that the pathogenic cascade was initiated before starting the treatment.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“… 34 Thus, clearance of HS from the brain at early disease stage might prevent the initiation of this pathogenic cascade. 20 , 31 In fact, the removal of deposited HS by JR-171 suppressed pathological changes in the brain and further prevented the loss of spatial learning ability in the Morris water maze test. Notably, in the 31-week treatment study, neuroinflammation and neurodegeneration were already present at the baseline (11 weeks of age), indicating that the pathogenic cascade was initiated before starting the treatment.…”
Section: Discussionmentioning
confidence: 97%
“…The pathogenic roles of DS and HS may vary across organs. 30 , 31 In the brain, HS deposition in neurons and glial cells induces neuroinflammation and neurodegeneration, 32 , 33 triggering CNS manifestations and progressive deterioration of disease conditions. 34 Thus, clearance of HS from the brain at early disease stage might prevent the initiation of this pathogenic cascade.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on the kind of deficient enzyme involved in the degradation of GAGs (due to mutations in the corresponding genes) and the nature of the accumulated GAG(s), 13 types and subtypes of MPS are currently distinguished [ 116 ]. All MPS types are severe diseases, and neurodegenerative processes, accompanied with mental deficits and disorders, occur in most of them [ 114 , 116 , 117 ]. Although MPS are monogenic diseases, recent studies indicated that the expression of hundreds of genes is changed (either up- or down-regulated) in each MPS type relative to the controls [ 118 ].…”
Section: Oxtr In Mucopolysaccharidosesmentioning
confidence: 99%
“…Treatment of MPS-II mice with a blood–brain-barrier-penetrable antibody (Pabinafusp Alfa) reduces HS levels in brain and prevents neurodegeneration and neurocognitive dysfunction [ 53 ]. The accumulation of HS in MPS-I, -II, -III, and -VII affects lysosomal functions, leading to numerous irreversible alterations within and outside cells (e.g., abnormal composition of membranes, intracellular vesicle trafficking, autophagy, mitochondrial dysfunction, oxidative stress, inflammation) [ 54 , 55 ].…”
Section: Glycosaminoglycans In Mpsmentioning
confidence: 99%